Learning Innovation through belajar.id Accounts to Improve Middle School Students’ Learning Engagement - Wahyu Prihatiningsih; Dian Hidayati; Muhammad Zuhaery (Universitas Pendidikan Ganesha, 2025)
The low utilization of digital learning platforms such as belajar.id account indicates that digital transformation at the junior high school level has not yet been fully optimized, thereby affecting students’ engagement in technology-based learning processes. This study aims to analyze and explore the implementation of Akun Belajar.id in enhancing student learning engagement. A qualitative approach with a case study method was employed. The research subjects included seventh, eighth, and ninth-grade students who had accessed belajar.id. Data were collected through observations, interviews, and documentation using interview guidelines, observation sheets, and documentation notes as instruments. Data analysis was conducted using Miles and Huberman’s interactive model with the assistance of ATLAS.ti 9 software to organize findings. The results reveal that the implementation of the platform’s utilization was carried out through structured stages of planning, organizing, implementation, and supervision. The use of Akun Belajar.id has been proven to increase students’ active participation and enrich digital learning experiences, although challenges remain, such as limited internet connectivity and difficulties in understanding certain materials. The conclusion emphasizes that Akun Belajar.id contributes positively to strengthening digital learning. The implication is that improved infrastructure support, mentoring, and the development of teacher and student competencies are required to optimize the platform’s utilization.